The cost of phage resistance in a plant pathogenic bacterium is context‐dependent - Meaden, Sean (Evolution, 2015)
Parasites are ubiquitous features of living systems and many parasites severely reduce the fecundity or longevity of their hosts. This parasite‐imposed selection on host populations should strongly favor the evolution of host resistance, but hosts typically face a trade‐off between investment in reproductive fitness and investment in defense against parasites. The magnitude of such a trade‐off is likely to be context‐dependent, and accordingly costs that are key in shaping evolution in nature may not be easily observable in an artificial environment. We set out to assess the costs of phage resistance for a plant pathogenic bacterium in its natural plant host versus in a nutrient‐rich, artificial medium. We demonstrate that mutants of Pseudomonas syringae that have evolved resistance via a single mutational step pay a substantial cost for this resistance when grown on their tomato plant hosts, but do not realize any measurable growth rate costs in nutrient‐rich media. This work demonstrates that resistance to phage can significantly alter bacterial growth within plant hosts, and therefore that phage‐mediated selection in nature is likely to be an important component of bacterial pathogenicity.